Effect of Unstable Surface Training on Walking Ability in Stroke Patients - Bang, Dae-Hyouk (J Phys Ther Sci, 2014)
[Purpose] The purpose of this study was to determine the effects of unstable surface training (UST) on walking ability in chronic stroke patients. [Subjects] The subjects were 12 stroke patients who were randomly divided into experimental (n(1)=6) and control (n(2)=6) groups. [Methods] The Subjects in both groups performed treadmill training for 30 minutes. The Subjects in the experimental group also performed UST after treadmill training, with the UST being performed for 10 minutes, five times per week, for four weeks. All subjects were evaluated with a 10-meter walk test, Timed Up and Go test and 6-minute walk test. The pared t-test was performed to test the significant differences between before and after the intervention. The independent t-test was conducted to test the significant differences between groups. [Results] Following the intervention, the experimental group showed significant differences in the Timed Up and Go test and 6-minute walk test. [Conclusion] The results of the study suggest that UST is an effective method for improvement of walking ability in chronic stroke patients.